Organizational Learning and Performance of Architectural Design Firms in Turkey - Ozturk, G. B.; Arditi, D.; Gunaydin, H. M.; Yitmen, I. (Asce-Amer Soc Civil Engineers, 2016)
Building up knowledge stocks in a firm is achieved through organizational learning, an important activity in a rapidly changing and competitive business environment. This paper investigates the impact of organizational learning on the performance of architectural design firms in Turkey. A questionnaire survey was administered to Turkish architectural design firms to collect information about the extent of learning at individual, project, and organizational levels and to measure the performance of the firm. Structural equation modeling (SEM) was used to analyze the data. Three hypotheses were tested to explore the interrelationships between learning at different levels and firm performance. The findings indicate that the extent of learning at the individual level positively affects the extent of learning at the project level, which in turn affects learning at the firm level. It is the extent of learning at the firm level that governs the firm's performance, while learning at individual and project levels have an indirect effect.
Keywords: Organizational learning; Firm performance; Architectural design firms; Structural equation modeling